Does connectivity exist for remnant boreal caribou (Rangifer tarandus caribou) along the Lake Superior Coastal Range? Options for landscape restoration - Drake, Christine C.; Manseau, Micheline; Klütsch, Cornelya F.C.; Priadka, Pauline; Wilson, Paul J.; Kingston, Steve; Carr, Natasha (Rangifer, 2018)
Genetic analysis can provide important information on the dynamic and spatial structure of groups of animals or populations. Little is known of the genetic population structure of caribou that inhabit the Lake Superior Coastal Range (LSCR) and the level of gene flow between individuals within the range and beyond. From a landscape perspective, this range is spatially isolated and genetic connectivity within the range is presumed limited due to large water crossings on Lake Superior. This study aims to answer if animal movement can be discerned, using genetic population and relatedness analyses, within and beyond the LSCR. Faecal and hair samples collected between 2005 and 2015 in Pukaskwa National Park were analyzed for genetic markers and compared to 131 unique genotypes previously obtained from both within the LSCR and in the two next closest ranges. Animals from one nearshore island (i.e. Otter) were more closely associated with offshore islands than other mainland caribou, likely a result of past movement and translocation rather than ongoing movement. Conversely, on another nearshore island (i.e. Pic), individuals assigned to a different genetic cluster and were related to animals further north outside the range, demonstrating some connectivity through the discontinuous distribution to the coast. Long-term population declines have been observed in the LSCR range despite genetic connectivity within the range and relatively low total habitat disturbance. Restoring connectivity of the LSCR so that it is not isolated from populations to the north is required for the recovery of the mainland portion of the coastal range. These genetic analyses provide some insights on where movements may occur and where landscape restoration efforts may best be directed to enhance connectivity.